Teaching Writing to the English Department Students of Sriwijaya State Polytechnics through a Process Genre Model Approach - Evi Agustinasari; Sri Gustiani; Yusri Yusri; Tiur Simanjuntak (Journal of English in Academic and Professional Communication, 2019)
The purpose of this study is to test whether the Process Genre Model Approach in teaching English Writing Subject to students of English Department at Sriwjaya State Polytechnic could improve the writing skills of the students. Using an experimental quantitative research method, this study tested the learning model to determine whether the model affected the dependent variable. There were 46 students involved in this study. They were equally divided and grouped into an experiment group and a control group. The experimental treatment was conducted in one semester studying period. The results revealed that the students’ writing skills in experimental classwas 77, while the control classwas 67.7, respectively, this study unveiled that the Process Genre Model was better for the treatment in teaching students’ writing skills for English Department students at Sriwijaya State Polytechnics. This approach also strengthened the field of students’ expertise via the genre model in the learning processes. Keywords: Teaching writing; polytechnics students; process genre model approach